Components of Phosphorus Loss From Agricultural Landscapes, and How to Incorporate Them Into Risk Assessment Tools - Reid, Keith; Schneider, Kimberly; McConkey, Brian (Frontiers in Earth Science, 2018)
Phosphorus (P) loss to surface freshwater is a key driver of environmental degradation, including blooms of both harmful (e.g. microcystis) and nuisance (e.g. cladophora) algae, along with the development of hypoxic zones that could significantly impact fish habitat . Mitigating P losses from agricultural land will require a detailed understanding of the forms (particulate versus dissolved), sources (soil erosion, desorption of soil P, dissolved P from fertilizer or manure application, or release from frozen vegetation) and transport pathways (surface runoff, or subsurface runoff through tile drains). This paper describes each of these components in detail, and discusses how this can guide the adoption of appropriate beneficial management practices to effectively reduce P losses. Further, it describes how this component structure has been incorporated into the Canadian national Indicator of Risk of Water Contamination by Phosphorus (IROWC-P) as an example of a risk assessment tool.